Isolation and Characterization of Salmonella Species from Street Food and Clinical Samples - Robin, Tunung (2006)
The aims of this study were to isolate and characterize Salmonella spp. from food sampled randomly from street vendors in Selangor, Malacca, Kuala Lumpur and Negeri Sembilan, and from clinical samples in a hospital in Klang, Selangor (collected from January to September 2004). A total of 24 Salmonella strains, belonging to seven different serotypes, were isolated from 129 different street-vended foods and drinks and 12 rectal swabs from hospital patients suspected with salmonellosis. The most frequently encountered serotype from street foods was Salmonella Biafra (66.7%) while the most frequently encountered serotype from clinical samples was Salmonella Typhi (66.7%). To the best of our knowledge, this is the first reported occurence of Salmonella Biafra in street foods in Malaysia. Other serotypes isolated from street foods were Salmonella Braenderup (25%) and Salmonella Weltevreden (8.3%), and from clinical samples were Salmonella Typhimurium (17%), Salmonella Paratyphi A (0.08%) and Salmonella Paratyphi B (0.08%). All isolates were tested for their resistance to the following 14 antibiotics: streptomycin, trimethoprim, sulphamethoxazole, tetracycline, cefuroxime, ciprofloxacin, ampicillin, chloramphenicol, gentamicin, rifampin, penicillin, nalidixic acid, norfloxacin and erythromycin. All strains (100%) were found resistant to the antibiotic rifampin. None of the strains were however resistant to cefuroxime. A dendrogram was generated for antibiotic resistances of the isolates, and six clusters were defined, with similarity levels ranging from 18.8% to 100%. Generally, street foods and clinical isolates tend to cluster apart. A dendrogram to cluster the antibiotics was also generated, and they could be grouped according to their classes based on mode of inhibition: cell wall synthesis, protein synthesis, or nucleic acid synthesis. The most related compounds were chloramphenicol and tetracycline (46.6% similarity), which is acceptable as they share the same mode of inhibition. Ampicillin was grouped in the same cluster at 13.5% similarity although of different inhibition mode, possibly due to cross-resistance. Out of the 24 isolates screened for the presence of plasmid, 15 harbored plasmids. The plasmid sizes ranged from 3.0 to 38.5 MDa. Randomly amplified polymorphic DNA (RAPD) and enterobacterial repetitive intergenic consensus (ERIC) analysis were performed for the molecular genetic typing of the strains. RAPD fingerprinting with the primers OPAR3 and OPAR8 produced a combination of 21 fingerprint patterns, while ERIC fingerprinting generated 19 patterns. Cluster analysis of S. Biafra showed that similar serotypes were found in different food samples collected at different locations. The likely source of this result was cross contamination during food handling. Cluster analysis of S. Typhi showed that all the serotypes were different, even though the location of sampling was the same. The results indicate multiple source of S. Typhi infection of the patients. From this study, RAPD was found to be more discriminative than ERIC.